Comparison of freeze drying and foam mat drying effects on characteristics of inulin from gembili (dioscorea esculenta). Issue 1 (July 2020) - Indah, N; Zainal,; Ganesa, D
Abstract: Gembili (Dioscorea esculenta) is of Dioscorea spp. which contains high inulin. Several factors can affect the physico-chemical characteristics of inulin, one of which is drying method. The purpose of this study was to compare the freeze drying and foam mat drying methods in producing of inulin from gembili (Dioscorea esculenta) based on physicochemical characteristics. Based on the analysis of inulin content of day the best gembili obtained, the samples dried using foam mat drying contained about 9, 38% inulin while those dried using freeze contained about 8, 66%inulin. The colors of dried samples were relatinglight as indicated by high L values 95.9% for freeze drying and 91, 3% for foam mat drying.